Impact of advanced age on the safety and effectiveness of paclitaxel‐eluting stent implantation in patients with ST‐segment elevation myocardial infarction undergoing primary angioplasty. Issue 6 (1st August 2013) - Dudek, Dariusz; Mehran, Roxana; Dziewierz, Artur; Witzenbichler, Bernhard; Brodie, Bruce R.; Kornowski, Ran; Fahy, Martin; Lansky, Alexandra J.; Rakowski, Tomasz; Legutko, Jacek; Bryniarski, Leszek; Stone, Gregg W.
<x xml:space="preserve">Abstract</x> Objectives To assess the impact of age on safety and efficacy of paclitaxel‐eluting stent (PES) implantation during primary percutaneous coronary intervention (PCI) in patients with ST‐segment elevation myocardial infarction (STEMI). Background The benefits of paclitaxel‐eluting stent (PES) implantation during primary PCI were confirmed by the long‐term results of the HORIZONS‐AMI trial. Whether the effects of PES are independent of age has not been reported. Methods Data on 3, 006 patients from the HORIZONS‐AMI study randomized in a 3:1 ratio to PES or bare‐metal stent (BMS) in whom at least one stent was implanted were assessed. There were 2, 302 (76.6%) patients <70, and 704 patients ≥70 years of age. Results At 3 years, among older patients a trend toward lower risk of major adverse cardiac events (MACE; death from any cause, stroke, reinfarction and unplanned revascularization for ischemia) related to PES use was observed (PES vs. BMS: 18.0% vs. 21.3%; P = 0.07). There was also a trend for reduction of MACE related to PES in older patients (26.4% vs. 33.1%; P = 0.09). Both, patients <70 and ≥70 years of age treated with PES were at lower risk for ischemic target vessel revascularization. However, a higher risk of major bleeding in elderly patients treated with PES was observed (P = 0.02 for interaction between age group and PES effects). No interaction between age and stent type in terms of the risk of other clinical end points, including all‐cause death, was confirmed. Conclusions For STEMI patients undergoing primary PCI, the implantation of PES as compared with BMS reduced ischemic TVR, and this effect was independent of age. [NCT00433966]. © 2013 Wiley Periodicals, Inc.